Variability and creativity in small-sided conditioned games among elite soccer players - Caso, S.; van der Kamp, J. (Psychology of Sport and Exercise, 2020)
Objective:Small-sided conditioned games (SSCG) in soccer are games with a small number of players, often played on smaller than regular pitches and with adapted rules. It has been argued that SSCG foster soccer players` physical, technical and tactical performances and creativity. This study tested the latter conjecture by analysing video-footage of individual actions of elite soccer players in 5 v 5, 6 v 6, 7 v 7 SSCG played during regular training sessions and 11-aside training matches. Based on the ecological dynamics approach, we hypothesized that smaller formats would result in players making more individual actions. We additionally anticipated that the smaller formats players would induce a larger repertoire of actions, that is, an increased variability of actions, and that such increase in variability would be associated with more creative actions. Along the same lines, we reasoned that midfielders would make more creative actions than defenders and attackers.